2017
DOI: 10.1007/s00244-017-0459-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomagnification of Mercury in Fish from Two Gold Mining-Impacted Tropical Marshes in Northern Colombia

Abstract: Total mercury concentrations (T-Hg) and stable isotope ratios (δN and δC) were analyzed in the muscle of fish, collected at two marshes impacted by gold mining in Northern Colombia, to evaluate the seasonal and spatial behavior of these variables and mercury biomagnification based on their relationship with δN ratios in the fish. There was not significant (p > 0.05) seasonal differences (dry and rainy season) in δN and δC values in none marsh, suggesting that these fish species keep a similar feed pattern with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
2
9
0
3
Order By: Relevance
“…In the case of mercury, the ingestion of high concentrations leads to higher risks since it tends to bioaccumulate through the food chain and can cause mutations (teratogenicity) [25]. It has been reported that up to 90% of the bioaccumulated mercury is incorporated into the digestive system through food [26].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of mercury, the ingestion of high concentrations leads to higher risks since it tends to bioaccumulate through the food chain and can cause mutations (teratogenicity) [25]. It has been reported that up to 90% of the bioaccumulated mercury is incorporated into the digestive system through food [26].…”
Section: Resultsmentioning
confidence: 99%
“…The isotopic measurements were expressed in parts per thousand (‰), using the delta (δ) unit relative to the deviation from international standard values PeeDee Belemnite Carbonate for δ 13 C and atmospheric N2 for δ 15 N (Méndez-Fernandez et al, 2012;Marrugo-Negrete et al, 2018). Based on replicate measurements of internal laboratory standards, experimental precision (SD) was < 0.09 for δ 13 C and < 0.36 for δ 15 N.…”
Section: Stable Isotope Analysesmentioning
confidence: 99%
“…The Hg low concentrations could be also related to the dominance of juvenile fish in the Archipelago, which reflect lower Hg concentrations compare to bigger ones as a consequence of bioaccumulation of Hg with age (Boush and Thieleke, 1983;Marrugo-Negrete et al, 2018). The abundance of juvenile fish in areas such as Almirante Bay is a result of dramatic decrease of larger predatory fish due to overfishing (Seemann et al, 2013).…”
Section: Hg Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentro de los elementos nocivos se encuentran metales como el Hg, los cuales han sido reportados de alto riesgo para la salud humana, debido a que en los tejidos de los peces de consumo se pueden llegar a encontrar en altas concentraciones (Olivero-Verbel et al, 2015;Vargas y Marrugo, 2019). ACTA BIOLÓGICA COLOMBIANA El MeHg puede ser bioacumulado en tejidos de peces como Prochilodus magdaleneae (bocachico) y Hoplias malabaricus (moncholo) (Marrugo-Negrete et al, 2018;Vargas y Marrugo, 2019), peces de alta importancia económica, gastronómica, cultural y comercial en las zonas de estudio. En Colombia, el bocachico habita las cuencas hidrográficas de los ríos Magdalena, Sinú y Atrato (Mojica et al, 2002;Maldonado-Ocampo et al, 2005;Román-Valencia, 1993).…”
Section: Introductionunclassified